2019
DOI: 10.5455/javar.2019.f363
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of BLRI Mastitis Test Kit at Bangladesh Livestock Research Institute Regional Station, Sirajganj

Abstract: Objective:The objective of this study was to develop a low-cost kit for the detection of subclinical mastitis (SCM) and to check its validity, reproducibility, and efficacy at the field level.Materials and Methods:A total of 550 quarter milk samples from crossbred dairy cows were collected, of which 400 milk samples were used to validate the newly developed BLRI mastitis test (BMT) kit to justify its efficacy as an individual test kit in detecting SCM based on somatic cell count (SCC) by direct microscopic cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Importantly, the costing and ease of access of the prototype reagents was lower as compared to commercially available mastitis test. Previous studies have demonstrated that screening of milk to detect subclinical mastitis is one of the most accurate methods (Kabir et al, 2019). Therefore, the newly developed milk screening reagent can be an independent, cheap and farmer friendly and alternative subclinical mastitis screening testing reagent readily available for use by rural livestock owners.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the costing and ease of access of the prototype reagents was lower as compared to commercially available mastitis test. Previous studies have demonstrated that screening of milk to detect subclinical mastitis is one of the most accurate methods (Kabir et al, 2019). Therefore, the newly developed milk screening reagent can be an independent, cheap and farmer friendly and alternative subclinical mastitis screening testing reagent readily available for use by rural livestock owners.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, CMT often has poor sensitivity on detecting subclinical mastitis and the yielded result could be difficult to interpret (Viguier et al, 2009). Early detection of subclinical mastitis is crucial to prevent the source of infection for herd mates, prevent transmission of zoonotic pathogens to human and minimize economic losses (Kabir et al, 2019).…”
Section: Investigation Of Serum and Milk Acute Phase Proteins Level I...mentioning
confidence: 99%
“…Immediately following the elevation of SCC in milk, the activity of proteolytic enzymes dramatically increases [10]. Automatic electronic counters and CMT are the most accurate and widely used methods for determining the amount of SCC [11]. During inflammation, mastitis releases several proteases and recruits polymorphonuclear neutrophils (PMNs) to migrate across the blood/milk barrier [12].…”
Section: Introductionmentioning
confidence: 99%